Virtual Machine Placement Using Multi-Objective Bat Algorithm With Decomposition in Distributed Cloud: MOBA/D for VMP - Venkataraman, NeelaNarayanan; Gopu, Arunkumar (International journal of applied metaheuristic computing, 2021)
Virtual machine placement in cloud computing considering multiple objectives is one of the significant issues in modern virtualized datacenters. Many businesses and organizations are outsourcing their computational workload to the cloud datacenters, which increases datacenter energy consumption and emission of CO2. In particular, allocating a virtual machine to a physical server in the community cloud model is even challenging due to its dynamic nature. Unlike public clouds, cloud servers are not always available in the same location. In this paper, a bio-inspired bat algorithm using decomposition (MOBA/D) is proposed to reduce three different objectives namely minimization of power consumption, minimization of network latency, and maximization of economical revenue. The performance of the proposed algorithm is compared with other multi-objective algorithms in terms of feasible solutions and execution time.